CASEFAT: Stata module for estimating the case fatality ratio of a new infectious disease - Griffin,J; Ghani,A
This program estimates the case fatality ratio, the proportion of cases who ultimately die of the disease, using incomplete data such as would be available part-way through an epidemic: some patients are observed to have died or recovered, but others are still ill. A Kaplan-Meier-like estimator is calculated according to the formulae given in: Ghani, A. C. et al. Methods for estimating the case fatality ratio for a novel emerging infectious disease.